2001
DOI: 10.1128/jmbe.v2.58
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of Active Learning Techniques to Introductory Microbiology

Abstract: While the traditional lecture format may be a successful way to teach microbiology to both medical and nursing students, it was not an effective means of learning for many prenursing and preprofessional students enrolled in either of the introductory microbiology courses at Ashland Community College, an open enrollment institution. The structure of both Medical Microbiology and Principles of Microbiology was redesigned to allow students to address the material in an active manner. Daily quizzes, student group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The comparison of student performance on the final examination indicates that team projects significantly improved the performance of the majority of students relative to the year before team projects were instituted (Table 1). Consistent with our results, several investigators found that cooperative learning approaches using small groups improved retention and final performance in different kinds of microbiology classes (5,6,19,32). However, this is not always the case.…”
Section: Discussionsupporting
confidence: 91%
“…The comparison of student performance on the final examination indicates that team projects significantly improved the performance of the majority of students relative to the year before team projects were instituted (Table 1). Consistent with our results, several investigators found that cooperative learning approaches using small groups improved retention and final performance in different kinds of microbiology classes (5,6,19,32). However, this is not always the case.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, researchers have shown that the use of CLGs leads students to evaluate their instructors more positively and may be associated with students engaging in such valued behaviors as completing the assigned reading and being prepared for class (e.g. Hoffman 2001;McKinney and Graham-Buxton 1993).…”
Section: Learningmentioning
confidence: 99%
“…Students have been shown to perform better and work harder at courses which they find relevant and interesting (8,9). The results of this survey suggest that the construct of the current Microbiology course allows students to develop the creative and analytical skills they require, while at the same time remaining stimulating.…”
Section: Discussionmentioning
confidence: 91%